Hipersuperfícies cujas geodésicas tangentes não cobrem o espaço ambiente - Viana, Emanuel Mendonça (2012)
Let I : ∑n → Mn+1 be an immersion of an n-dimensional connected manifold ∑ in an (n + 1)-dimensional connected completed Riemannian manifold M without conjugate points. Assume that the union of geodesics tangent to I does not cover M. Under these hypotheses we have two results: 1. M is simply connected provided that the universal covering of ∑ is compact. 2. If I is a proper embedding and M is simply connected, then I(∑) is a normal graph over an open subset os a geodesic sphere. Furthermore, there exists an open star-shaped set A M such that A is a manifold with the boundary I(∑).